The gendered brain : the new neuroscience that shatters the myth of the female brain - Rippon, Gina 1950- (London : Vintage, 2020)
Barbie or Lego? Reading maps or reading emotions? Do you have a female brain or a male brain? Or is that the wrong question? On a daily basis we face deeply ingrained beliefs that our sex determines our skills and preferences, from toys and colours to career choice and salaries. But what does this mean for our thoughts, decisions and behaviour? Using the latest cutting-edge neuroscience, Gina Rippon unpacks the stereotypes that bombard us from our earliest moments and shows how these messages mould our ideas of ourselves and even shape our brains. Rigorous, timely and liberating, The Gendered Brain has huge repercussions for women and men, for parents and children, and for how we identify ourselves.
Keywords: NEUROPSICOLOGIA; CEREBRO -- PSICOFISIOLOGÍA; CEREBRO -- DIFERENCIAS SEXUALES; DIFERENCIAS SEXUALES; ESTEREOTIPOS (PSICOLOGÍA SOCIAL)